Augmented reality for minimally invasive spinal surgery - Avrumova, Fedan; Lebl, Darren R. (Frontiers in Surgery, 2023)
Background Augmented reality (AR) is an emerging technology that can overlay computer graphics onto the real world and enhance visual feedback from information systems. Within the past several decades, innovations related to AR have been integrated into our daily lives; however, its application in medicine, specifically in minimally invasive spine surgery (MISS), may be most important to understand. AR navigation provides auditory and haptic feedback, which can further enhance surgeons’ capabilities and improve safety. Purpose The purpose of this article is to address previous and current applications of AR, AR in MISS, limitations of today's technology, and future areas of innovation. Methods A literature review related to applications of AR technology in previous and current generations was conducted. Results AR systems have been implemented for treatments related to spinal surgeries in recent years, and AR may be an alternative to current approaches such as traditional navigation, robotically assisted navigation, fluoroscopic guidance, and free hand. As AR is capable of projecting patient anatomy directly on the surgical field, it can eliminate concern for surgeon attention shift from the surgical field to navigated remote screens, line-of-sight interruption, and cumulative radiation exposure as the demand for MISS increases. Conclusion AR is a novel technology that can improve spinal surgery, and limitations will likely have a great impact on future technology.